Differences in the Influence of Core Stability and Balance Training Training on the Risk of Falling in the Elderly - Linda Sahru Ramadani; Dwi kurniawati; Nur Basuki (Jurnal Terapi Wicara dan Bahasa, 2023)
Background of the problem: The aging process causes a decrease in the sensory system, musculoskeletal system, and neurological system which will cause balance disorders and also the risk of falling, to reduce these problems, physical activity must be increased, to improve this there are several exercises such as core stability and balance training. Research Objectives: This study aims to determine differences in the effect of core stability training and balance training on reducing the risk of falling in the elderly. Research Methods: The research design was two group pre and post test design. Research Subjects: The subjects in this study were the elderly who were at risk of falling in the Independent Children's Social Service Institution for the Elderly Social Service "Pucang Gading" who met the inclusion criteria. The number of subjects as many as 30 subjects were divided into 2 groups divided by randomization. Group I was given core stability training and group II was given balance training. Fall risk measurement uses the Time Up and Go Test (TUGT). Research Results: The results of different test groups of core stability and balance training post test using the Independent T-Test showed p = 0.00 (p = <0.05). This shows that there is a difference in the effect of core stability training and balance training on reducing the risk of falling in the elderly. The results of the mean difference in the core stability and balance training groups showed that the core stability group was greater than the balance training group. Conclusion: Core stability has more influence on reducing the risk of falling in the elderly than balance training Group